Rhizoglyphus echinopus - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
Rhizoglyphus echinopus (Fumouze & Robin, 1868) Width: 944.84 ± 0.33, length: 755.63 ± 0.21 (n = 10). Specimens examined Centrum / Uzunkavak Village garlic storage, 10.IX.2015, (1 ♀); Taşköprü / Akdoğan Village garlic storage, 16.IX.2015 (1 ♀); Centrum / Uzunkavak Village garlic storage, 10.IX.2015 (1 ♂); Taşköprü / Alatarla Village garlic storage, 20.X.2015 (1 ♂). Comments Rhyzoglyphus echinopus was reported for the first time by Çobanoğlu (1996) on wheat and stored sunflower in Edirne. Çobanoğlu and Bayram (1998) found the species in tuberous ornamental plants. In this study, R. echinopus has been collected just in the stored garlic heads.

{"references": ["Cobanoglu, S. (1996) Typhloctonus Muma, 1961 (Acarina: Phytoseiidae) species, from thrace of Turkey. Doga, Turk Tarim ve Ormancilik Dergisi, 20: 353 - 357.", "Cobanoglu, S. & Bayram, S. (1998) Mites (Acari) and flies (Insecta: Diptera) from natural edible mushrooms (Morchella: Ascomycetes) in Ankara, Turkey. Bulletin & Annales de la Societe Royale Belge d'Entomologi, 134 (3): 187 - 198."]}

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 217, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998
Keywords: Rhizoglyphus; Arthropoda; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Rhizoglyphus echinopus; Taxonomy; Acaridae; 2. Zero hunger